Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Produk Pisang Keju Lintang Kota Malang - Adhim, Mohammad Bashoril; Khalikussabir, Khalikussabir; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to describe and analyze the implementation of marketing strategies in increasing sales of Pisang Keju Lintang products in Malang City. The type of research used in this study is qualitative research. The data analysis method in this study is SWOT analysis, IFE and EFE Matrix and Grand Strategy matrix. Based on the results of the research and discussion that have been carried out, it can be concluded that the marketing strategy in increasing product sales is to use an aggressive strategy with considerations in determining the strategy, namely the business has strengths that include products, in this case regarding brands, packaging and quality / quality of products offered. Strengths in promotion in this case promotional activities carried out by the owner online, activities or distribution channels include location and transportation, while the price factor includes discounts, bonuses given and setting selling prices. Weaknesses of the business regarding offline promotional activities, where the implementation of the promotion has not been maximally carried out by the owner. Opportunities owned by the business are regarding economic conditions, namely the existence of per capita income and economic growth that shows an increase. Government policies and training activities provided by the local government. The opportunities from demographic factors are the use of technology in the field of marketing. Threatening factors are the existence of competitors from similar companies and the economic conditions of the community that affect purchasing power. Keywords: Marketing Strategy, Sales and Products of Lintang Cheese Bananas, Malang City